2015
DOI: 10.3390/ijms16011806
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Protein 1 Regulates Gene Expression Related to Fatty Acid Metabolism in Goat Mammary Epithelial Cells

Abstract: Specificity protein 1 (SP1) is a ubiquitous transcription factor that plays an important role in controlling gene expression. Although important in mediating the function of various hormones, the role of SP1 in regulating milk fat formation remains unknown. To investigate the sequence and expression information, as well as its role in modulating lipid metabolism, we cloned SP1 gene from mammary gland of Xinong Saanen dairy goat. The full-length cDNA of the SP1 gene is 4376 bp including 103 bp of 5'UTR, 2358 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…The important role of PPAR␥ in the mouse indicated by the in silico analysis is not supported by experimental data, as discussed above. At least one TFBS for the Sp1 was present in all milk fat-related genes, supporting a role for this TF, as recently demonstrated (257).…”
Section: Other Tfsupporting
confidence: 79%
See 1 more Smart Citation
“…The important role of PPAR␥ in the mouse indicated by the in silico analysis is not supported by experimental data, as discussed above. At least one TFBS for the Sp1 was present in all milk fat-related genes, supporting a role for this TF, as recently demonstrated (257).…”
Section: Other Tfsupporting
confidence: 79%
“…Very recently it was demonstrated that the Specificity protein 1 (Sp1) also plays a role in controlling milk fat synthesis in goat mammary cells (257). The overexpression of Sp1 increased the transcription of several genes involved in milk fat synthesis, including PPARG, whereas the SREBF1 remained unaffected and the NR1H2 was downregulated (257).…”
Section: Other Tfmentioning
confidence: 99%
“…10,47,66 With increaesd miRNA research, researchers are trying to combine the data from different approaches (genomics, proteomics, and miRNA genomics) to obtain more effective data for practical application. 57,60 Although there are many methods used to analyze mRNA and miRNA for lipid metabolism 55 , there has been no miRNA-mRNA regulation analysis performed in milk goats.…”
Section: Discussionmentioning
confidence: 99%
“…66 In brief, GMEC were transfected with miR-148a, miR-17-5p mimic or inhibitor, were cleaned several times in PBS (phosphate buffer solution), and were fixed in 10% paraformaldehyde for 30 minutes. Afterwards, cells were stained using 10% oil red O in isopropanol for 10 minutes, were cleaned by PBS, and were detected microscopically.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Previous research illustrated that miRNA plays an important role in mammary development and lactation [35,36,37]. For instance, Avril-Sassen et al screened and compared the expression of 102 miRNA in different stages of lactation in mice and speculated that some differentially-expressed miRNA were related to fatty acid metabolism [38].…”
Section: Discussionmentioning
confidence: 99%